Propagation characteristics of ultrasonic P-wave velocity in artificial jointed coal briquettes. (15th July 2020) - Sun, Xiaoyuan; Chen, Gengyue; Li, Jihui; Xu, Xiaomeng; Fu, Shuai; Xie, Jianlin; Liang, Lei
Abstract: Abundant engineering practice shows that coal and rock dynamic disasters often occur in fault zones; hence, the detection of faults in coal mines is important. As an essential branch of seismic tomographic application, research shows that ultrasonic P-wave velocity can detect mine faults and provide technical support for dynamic disaster prewarning systems. Traditional P-wave testing mostly takes rock or raw coal as the research object, which has some shortcomings in controllability, homogeneity and comparability. This paper compares the difference in ultrasonic P-wave propagation velocity in jointless and jointed briquettes through laboratory research, focuses on the effect of macro-joints on P-wave velocity and makes a preliminary theoretical analysis. The results show that: (i) the three-dimensional P-wave velocity throughout a jointless briquette specimen is similar, which reflects the high homogeneity of this medium and avoids the influence of the random distribution of primary bedding, joints and structural planes; (ii) the P-wave velocity in jointless and jointed briquettes is positively correlated with density and forming pressure, and is negatively correlated with the angle between the ultrasonic wave and the joint surface in a sample and (iii) when the P-wave encounters the macroscopic joint surface, it may reflect and refract, changing the propagation direction and inducing wave mode conversion. This study provides the necessary technical support and a theoretical guide to optimise acoustic property analysis of coal and rock as well as a field application for seismic tomography technology.